Keeping Schools for Blind Students Vital in an Era of Inclusion: Key Elements for Success. (March 2022) - Miyauchi, Hisae; Fast, Danene; Wild, Tiffany
Introduction: This research aims to learn what schools for blind students in the United States are currently doing to teach students with visual impairments and further explore the services these schools provide in their states.Methods: This research used qualitative interviews with school administrators, staff members, and teachers at four schools for blind students in the United States. A constant comparison model was used to analyze common themes and trends within the data collected, allowing us to capture the voiced experiences of the interviewees.Results: All schools included in this research have built the capacity to serve a wide range of students with visual impairments through both on-campus programs and outreach services. To provide high-quality services, the on-campus programs and the outreach services embraced symbiosis with one another. In parallel to this effort, schools focused on building partnerships with districts and helped build capacity through indirect services.Discussion: Underlying ideologies within schools for blind students were the value of inclusion, belief in every student receiving a quality education, and aspiration towards schools for blind students to stay relevant in an era of inclusion. Schools were led by individuals who possessed inspirational and strategic thinking.Implications for Practitioners: This research documents the effective ways specialized schools for blind students are relevant in an era of inclusion, documenting the importance of creating new paths within traditional programs. This research outlines successful practices and ideologies that can be implemented by specialized schools, while acknowledging traditional on-campus programming combined with inclusive outreach models to create sustainable programming for all students with visual impairments throughout a state.